The degree of whey hydrolysis does not uniformly affect in vitro basophil and T cell responses of cow's milk‐allergic patients. Issue 4 (April 2014) - Meulenbroek, L. A. P. M.; Oliveira, S.; den Hartog Jager, C. F.; Klemans, R. J. B.; Lebens, A. F. M.; van, T.; Knulst, A. C.; Bruijnzeel‐Koomen, C. A. F. M.; Garssen, J.; Knippels, L. M. J.; van, E.
Summary Background Several studies investigated whether hydrolysed proteins can induce tolerance to cow's milk (CM) in children at risk of developing CM allergy. Due to methodological problems and inconsistent findings, the evidence for a tolerogenic effect is limited. A major problem is that different hydrolysates may give different outcomes due to variations in their production and composition. Objective The aim of the study was to investigate the effect of the degree of hydrolysis on the allergenicity and immunogenicity of whey hydrolysates. Methods The hydrolysis of whey was stopped at different time‐points between 1 and 60 min. In 18 CM allergic patients, the allergenicity of the hydrolysates was determined by immunoblot and the basophil activation test. To test immunogenicity, CM‐specific T cell lines were generated. Results In most patients, increasing time of hydrolysis decreased IgE recognition and basophil activation. However, in five patients, hydrolysed proteins induced more basophil activation than non‐hydrolysed proteins. The immunoblot data indicated that these patients recognized either a 25‐ to 30‐kDa degradation product of casein or a 10‐kDa degradation product of whey. Although T cell activation was decreased in all patients over time, half of them still showed a positive response to the proteins after 60 min of hydrolysis. Conclusion Increasing the time of hydrolysis reduces both allergenicity and immunogenicity of whey hydrolysates in most but not all patients. This indicates that not the degree of hydrolysis is decisive but the presence and stability of IgE and T cell epitopes in the hydrolysate recognized by individual patients.